Evaluation of the nonverbal reading approach for two 12 to 13-year-old students with ASD. (January 2015) - Leytham, Patrick A.; Pierce, Tom; Baker, Josh; Miller, Susan; Tandy, Dick
Highlights: Teacher-led and technology-aided components of the NRA were effective. Teacher-led component more effective than technology-aided component. Positive increase in attitudes by the teacher to implement the NRA. Abstract: The ability of students with autism spectrum disorder (ASD) to identify and comprehend text varies across age level and severity of disability. Phonics-based approaches that utilize technology-aided instruction have been used to assist younger students with ASD identify and comprehend text. However, limited research exists on the effectiveness of a phonics-based approach to improve the word identification abilities of older students with ASD. The Nonverbal Reading Approach (NRA) is a method that teaches students with communicative impairments, such as ASD, to identify words by sounding out individual phonemes using internal speech. A multiple probe design across participants combined with an adapted alternating treatment design was used to determine whether or not the NRA would be effective for two 12 to 13-year-old students with ASD. Results indicate that the teacher-led and technology-aided components of the NRA were effective for improving participants' word identification abilities.